The Long-Term Effects of War on Foreign Direct Investment and Economic Development: Evidence from Vietnam - Cuong Viet Nguyen; Tuyen Quang Tran; Huong Van Vuc (Global Labor Organization (GLO), 2022)
In this study, we find that the negative effect of unexploded ordnance (UXO) on the geographical density of foreign direct investment and large firms is a new channel through which the war legacy impedes local development in Vietnam. A 1% increase in the proportion of UXO-contaminated area leads to a 0.78% relative decrease in the density of FDI firms within districts. Point estimates for the elasticity of the density of joint-venture FDI firms and state-owned enterprise (SOEs) due to UXO are smaller, equal to -0.56 and -0.54. Consequently, a 1% increase in the proportion of UXO-contaminated areas leads to a 0.46% relative decrease in the intensity of nighttime light.
Keywords: R12; O12; O15; 330; War; FDI; unexploded ordnance; local development; Vietnam